TINJAUAN LITERATUR SISTEMATIS: ANALISIS SWOT DALAM MANAJEMEN KEUANGAN PERUSAHAAN - Rachmad Zainuri; Pompong Budi Setiadi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
SWOT analysis is an analytical method used to evaluate the 'strengths', 'weaknesses', 'opportunities', and 'threats' involved in an organization, plan, project, person, or business activity. The aim of this paper is to review the body of knowledge and academic research on SWOT analysis. This shows significant concerns and trends and knowledge gaps around SWOT analysis. Applying PRISMA's guidelines for conducting and summarizing systematic reviews, literature reviews were carried out systematically. Based on a systematic search of the Springer database, a total of 21 articles were included. Within the topics of conceptual models, research frameworks, and measurement and evaluation of SWOT analysis, a research agenda for future studies in this field is offered.